Composite automotive sound-deadening carpet, method of manufacture and use

CN119141991BActive Publication Date: 2026-09-22NANJING YUNCHI AUTOMOTIVE PARTS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411288978.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2026-09-22
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

[0004]基于背景技术存在隔音效果差,不耐低温的问题,本发明提出了一种复合材料汽车隔音地毯、制备方法和应用

Benefits of technology

通过聚丙烯树脂、聚碳酸酯、改性淀粉、改性蒙脱土、立构聚乳酸纤维和添加剂制备出中间层,且中间层采用的蜂窝结构层,利用其蜂窝结构,可以在中间层的内部形成无数个隔音空腔,提升隔音效果,而且采用面层、中间层和防滑层的组合,再加上内部添加的增强材料,可以提升地毯的耐低温性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119141991B_ABST
    Figure CN119141991B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of automobiles, and particularly relates to a composite material automobile sound insulation carpet, a preparation method and application. In view of the problems of poor sound insulation effect and poor low-temperature resistance, the following scheme is provided. The sound insulation carpet comprises a surface layer, an intermediate layer bonded at the bottom of the surface layer, and an anti-skid layer bonded at the bottom of the intermediate layer. The intermediate layer comprises a honeycomb structure layer and a rubber plate layer bonded at the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 35-45 parts of polypropylene resin, 20-30 parts of polycarbonate, 10-20 parts of modified starch, 5-15 parts of modified montmorillonite, 5-15 parts of stereotactic polylactic acid fiber, and 5-10 parts of additives. The honeycomb structure layer used in the intermediate layer can form numerous sound insulation cavities inside the intermediate layer, improving the sound insulation effect. Moreover, the combination of the surface layer, the intermediate layer and the anti-skid layer, together with the internal addition of reinforcing materials, can improve the low-temperature resistance of the carpet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of automotive technology, and in particular to a composite material automotive sound insulation carpet, its preparation method, and its application. Background Technology

[0002] Chinese patent application number 202310079536.6 discloses a processing method for automotive carpets, an automotive carpet, and a vehicle. The processing method includes the following steps: fabricating a carpet cavity mold, the carpet cavity mold including an upper mold and a lower mold, the upper mold and the lower mold forming a sealed cavity after being closed; preparing a PU mixture; injecting the PU mixture into the sealed cavity for mixing, foaming, skinning, and curing to form a surface layer; and placing the surface layer into a carpet backing foaming mold for PU foaming and lamination to form a backing layer. According to the processing method for automotive carpets of this invention, automotive carpets are manufactured based on the principle of PU cavity mixing and skinning. The customized automotive carpet texture is not affected by the thickness of the raw materials, the molding structure, or the depth of the surface texture, which can improve the plasticity and wear resistance of the surface layer. Simultaneously, the carpet's softness and hardness are adjustable, meeting customers' requirements for comfort underfoot.

[0003] However, there are some problems with the processing method of the car carpet, the car carpet itself, and the vehicle. For example, its sound insulation effect is poor, and it cannot reduce the noise inside the car, affecting the experience of the driver and passengers. Moreover, it is prone to becoming brittle and damaged in low-temperature environments. Summary of the Invention

[0004] Based on the problems of poor sound insulation and low temperature resistance in the background technology, this invention proposes a composite material automotive sound insulation carpet, its preparation method, and its application.

[0005] The present invention proposes a composite material automotive sound insulation carpet, which includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 35 to 45 parts of polypropylene resin, 20 to 30 parts of polycarbonate, 10 to 20 parts of modified starch, 5 to 15 parts of modified montmorillonite, 5 to 15 parts of stereopolylactic acid fiber, and 5 to 10 parts of additives, including toughening agents, fillers, lubricants, antioxidants, and processing aids. The anti-slip layer comprises the following components by weight: 45-55 parts waste tire particles, 25-35 parts epoxy resin, 10-20 parts PPS fiber, 5 parts sulfur, and 4 parts modified carbon black. The intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber, and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Furthermore, the combination of the surface layer, intermediate layer, and anti-slip layer, along with the internal reinforcing materials, can improve the carpet's low-temperature resistance.

[0006] Preferably, the surface layer is made of a blend of corn fiber, bamboo fiber, nylon fiber and polypropylene fiber, which can enhance the wear resistance and practicality of the surface layer.

[0007] Preferably, the modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester, and ethanol, which facilitates modification and enhances compatibility.

[0008] Preferably, the modified starch is prepared by: obtaining corn starch and potato starch, pouring them into 30 to 50 times their weight of deionized water, and stirring at high speed using a mixer at a speed of 1200 rpm to 1500 rpm. During the stirring process, the temperature is raised to 80°C and kept warm for 15 minutes to obtain a starch microsphere emulsion. Acrylic acid, dehydrated sorbitan fatty acid ester, and ethanol are poured into a reaction vessel and stirred and mixed at 50°C at a speed of 500 rpm to 700 rpm. After 15 minutes, the starch microsphere emulsion is poured into the reaction vessel and stirred for another 30 minutes at a speed of 800 rpm to 900 rpm. The mixture is then cooled to room temperature, filtered to obtain starch microspheres and filtrate. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain modified starch, which can effectively modify starch.

[0009] Preferably, the raw materials for producing the modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water, which facilitates the modification of montmorillonite.

[0010] Preferably, the modified montmorillonite is prepared as follows: montmorillonite is poured into a grinding device and ground at room temperature. During the grinding process, quaternary phosphine salt, sodium pyrophosphate, and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water, and ultrasonic treatment is performed using an ultrasonic device. After heating to 70°C, the powder is allowed to cool and settle naturally. Finally, the powder is filtered, centrifuged, washed, dried, and sieved to obtain modified montmorillonite, which can enhance the performance of montmorillonite.

[0011] Preferably, the modified carbon black is prepared by: pouring silane coupling agent and water into a mixer and stirring to form a silane coupling agent solution; then adjusting the pH of the silane coupling agent solution to 4; hydrolyzing the silane coupling agent to form a silane coupling agent hydrolysate; diluting the hydrolysate in an ethanol solution and adjusting the pH to 4; then adding carbon black; mixing; pouring the mixture into a reaction vessel and stirring to obtain a slurry; heating the reaction vessel to 75°C and continuing the stirring reaction to allow the silane coupling agent to graft onto the surface of the carbon black; finally drying and pulverizing to obtain modified carbon black, which is beneficial for improving the efficiency of carbon black.

[0012] A method for preparing a composite material automotive sound insulation carpet includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives to mix, and divide the mixture into three parts. One part of the mixture is poured into the honeycomb structure mold to make a honeycomb structure layer, and the other two parts of the mixture are made into a plastic sheet layer. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: The waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black are mixed and then poured into a mold that can make anti-slip texture, and extruded to obtain an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

[0013] Preferably, in step S2, the mixing speed is controlled at 600 rpm to 700 rpm, and the three mixtures are evenly distributed.

[0014] Preferably, composite material automotive sound insulation carpets are used in automobiles.

[0015] The beneficial effects of this invention are: The intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Furthermore, the combination of the surface layer, intermediate layer and anti-slip layer, along with the internal reinforcement materials, can improve the carpet's low-temperature resistance. Attached Figure Description

[0016] Figure 1 This is a flowchart illustrating the workflow proposed in this invention. Detailed Implementation

[0017] The present invention will be further explained below with reference to specific embodiments.

[0018] Reference Figure 1 Example 1 This embodiment proposes a composite material automotive sound insulation carpet, which includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 37 parts polypropylene resin, 23 parts polycarbonate, 15 parts modified starch, 12 parts modified montmorillonite, 7 parts stereopolylactic acid fiber and 6 parts additives, including toughening agents, fillers, lubricants, antioxidants and processing aids. The anti-slip layer contains the following components by weight: 49 parts waste tire pellets, 31 parts epoxy resin, 11 parts PPS fiber, 5 parts sulfur, and 4 parts modified carbon black. The surface layer is a blend of corn fiber, bamboo fiber, nylon fiber, and polypropylene fiber. The modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester, and ethanol. The preparation method of the modified starch is as follows: obtain corn starch and potato starch, pour them into 30 to 50 times their weight of deionized water, and stir at high speed using a mixer at 1300 rpm. During the stirring process, raise the temperature to 80°C and maintain... Stirring at room temperature for 15 minutes yields a starch microsphere emulsion. Acrylic acid, sorbitan fatty acid ester, and ethanol are added to a reaction vessel and stirred at 50°C and 500 rpm for 15 minutes. The starch microsphere emulsion is then added to the reaction vessel and stirred for another 30 minutes at 900 rpm. After cooling to room temperature, starch microspheres and the filtrate are obtained by suction filtration. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain modified starch. The raw materials for modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water. The preparation method of modified montmorillonite is as follows: under room temperature conditions... The following steps are performed: Montmorillonite is poured into a grinding device for grinding. During the grinding process, quaternary phosphine salt, sodium pyrophosphate, and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water, and ultrasonic treatment is performed using an ultrasonic device. After heating to 70°C, it is allowed to cool and settle naturally. Finally, it is filtered, centrifuged, washed, dried, and sieved to obtain modified montmorillonite. The preparation method for modified carbon black is as follows: Silane coupling agent and water are poured into a mixer and stirred to form a silane coupling agent solution. The pH value of the silane coupling agent solution is then adjusted to 4. After hydrolysis of the silane coupling agent, a silane coupling agent hydrolysate is formed. This hydrolysate is diluted in an ethanol solution, and the pH value is adjusted to 4. Then carbon black is added, mixed, and poured into a reaction vessel for stirring to obtain a slurry. The reaction vessel is heated to 75°C, and stirring is continued to allow the silane coupling agent to graft onto the carbon black surface. Finally, it is dried and pulverized to obtain modified carbon black. An intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber, and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Moreover, the combination of the surface layer, intermediate layer, and anti-slip layer, along with the internal reinforcing materials, can improve the carpet's low-temperature resistance.

[0019] A method for preparing a composite material automotive sound insulation carpet includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives and mix to obtain a mixture. Divide the mixture into three parts. Pour one part of the mixture into a honeycomb structure mold to make a honeycomb structure layer. The other two parts of the mixture are used to make a rubber sheet layer. The mixing speed is controlled at 600rpm~700rpm. The three parts of the mixture are evenly distributed. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: The waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black are mixed and then poured into a mold that can make anti-slip texture, and extruded to obtain an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

[0020] Composite material automotive sound insulation carpets are used in automobiles.

[0021] Reference Figure 1 Example 2 This embodiment proposes a composite material automotive sound insulation carpet, which includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 35 parts polypropylene resin, 22 parts polycarbonate, 13 parts modified starch, 11 parts modified montmorillonite, 12 parts stereopolylactic acid fiber and 7 parts additives, including toughening agents, fillers, lubricants, antioxidants and processing aids. The anti-slip layer contains the following components by weight: 50 parts waste tire pellets, 28 parts epoxy resin, 13 parts PPS fiber, 5 parts sulfur, and 4 parts modified carbon black. The surface layer is a blend of corn fiber, bamboo fiber, nylon fiber, and polypropylene fiber. The modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester, and ethanol. The preparation method of the modified starch is as follows: obtain corn starch and potato starch, pour them into 30 to 50 times their weight of deionized water, and stir at high speed using a mixer at 1300 rpm. During the stirring process, raise the temperature to 80°C and maintain... Stirring at room temperature for 15 minutes yields a starch microsphere emulsion. Acrylic acid, sorbitan fatty acid ester, and ethanol are added to a reaction vessel and stirred at 50°C and 500 rpm for 15 minutes. The starch microsphere emulsion is then added to the reaction vessel and stirred for another 30 minutes at 900 rpm. After cooling to room temperature, starch microspheres and the filtrate are obtained by suction filtration. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain modified starch. The raw materials for modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water. The preparation method of modified montmorillonite is as follows: under room temperature conditions... The following steps are performed: Montmorillonite is poured into a grinding device for grinding. During the grinding process, quaternary phosphine salt, sodium pyrophosphate, and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water, and ultrasonic treatment is performed using an ultrasonic device. After heating to 70°C, it is allowed to cool and settle naturally. Finally, it is filtered, centrifuged, washed, dried, and sieved to obtain modified montmorillonite. The preparation method for modified carbon black is as follows: Silane coupling agent and water are poured into a mixer and stirred to form a silane coupling agent solution. The pH value of the silane coupling agent solution is then adjusted to 4. After hydrolysis of the silane coupling agent, a silane coupling agent hydrolysate is formed. This hydrolysate is diluted in an ethanol solution, and the pH value is adjusted to 4. Then carbon black is added, mixed, and poured into a reaction vessel for stirring to obtain a slurry. The reaction vessel is heated to 75°C, and stirring is continued to allow the silane coupling agent to graft onto the carbon black surface. Finally, it is dried and pulverized to obtain modified carbon black. An intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber, and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Moreover, the combination of the surface layer, intermediate layer, and anti-slip layer, along with the internal reinforcing materials, can improve the carpet's low-temperature resistance.

[0022] A method for preparing a composite material automotive sound insulation carpet includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives and mix to obtain a mixture. Divide the mixture into three parts. Pour one part of the mixture into a honeycomb structure mold to make a honeycomb structure layer. The other two parts of the mixture are used to make a rubber sheet layer. The mixing speed is controlled at 600rpm~700rpm. The three parts of the mixture are evenly distributed. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: The waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black are mixed and then poured into a mold that can make anti-slip texture, and extruded to obtain an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

[0023] Composite material automotive sound insulation carpets are used in automobiles.

[0024] Reference Figure 1 Example 3 This embodiment proposes a composite material automotive sound insulation carpet, which includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 36 parts polypropylene resin, 22 parts polycarbonate, 12 parts modified starch, 10 parts modified montmorillonite, 13 parts stereopolylactic acid fiber and 7 parts additives, including toughening agents, fillers, lubricants, antioxidants and processing aids. The anti-slip layer contains the following components by weight: 50 parts waste tire pellets, 28 parts epoxy resin, 13 parts PPS fiber, 5 parts sulfur, and 4 parts modified carbon black. The surface layer is a blend of corn fiber, bamboo fiber, nylon fiber, and polypropylene fiber. The modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester, and ethanol. The preparation method of the modified starch is as follows: obtain corn starch and potato starch, pour them into 30 to 50 times their weight of deionized water, and stir at high speed using a mixer at 1300 rpm. During the stirring process, raise the temperature to 80°C and maintain... Stirring at room temperature for 15 minutes yields a starch microsphere emulsion. Acrylic acid, sorbitan fatty acid ester, and ethanol are added to a reaction vessel and stirred at 50°C and 500 rpm for 15 minutes. The starch microsphere emulsion is then added to the reaction vessel and stirred for another 30 minutes at 900 rpm. After cooling to room temperature, starch microspheres and the filtrate are obtained by suction filtration. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain modified starch. The raw materials for modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water. The preparation method of modified montmorillonite is as follows: under room temperature conditions... The following steps are performed: Montmorillonite is poured into a grinding device for grinding. During the grinding process, quaternary phosphine salt, sodium pyrophosphate, and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water, and ultrasonic treatment is performed using an ultrasonic device. After heating to 70°C, it is allowed to cool and settle naturally. Finally, it is filtered, centrifuged, washed, dried, and sieved to obtain modified montmorillonite. The preparation method for modified carbon black is as follows: Silane coupling agent and water are poured into a mixer and stirred to form a silane coupling agent solution. The pH value of the silane coupling agent solution is then adjusted to 4. After hydrolysis of the silane coupling agent, a silane coupling agent hydrolysate is formed. This hydrolysate is diluted in an ethanol solution, and the pH value is adjusted to 4. Then carbon black is added, mixed, and poured into a reaction vessel for stirring to obtain a slurry. The reaction vessel is heated to 75°C, and stirring is continued to allow the silane coupling agent to graft onto the carbon black surface. Finally, it is dried and pulverized to obtain modified carbon black. An intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber, and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Moreover, the combination of the surface layer, intermediate layer, and anti-slip layer, along with the internal reinforcing materials, can improve the carpet's low-temperature resistance.

[0025] A method for preparing a composite material automotive sound insulation carpet includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives and mix to obtain a mixture. Divide the mixture into three parts. Pour one part of the mixture into a honeycomb structure mold to make a honeycomb structure layer. The other two parts of the mixture are used to make a rubber sheet layer. The mixing speed is controlled at 600rpm~700rpm. The three parts of the mixture are evenly distributed. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: The waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black are mixed and then poured into a mold that can make anti-slip texture, and extruded to obtain an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

[0026] Composite material automotive sound insulation carpets are used in automobiles.

[0027] Reference Figure 1 Example 4 This embodiment proposes a composite material automotive sound insulation carpet, which includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 35 parts polypropylene resin, 20 parts polycarbonate, 15 parts modified starch, 10 parts modified montmorillonite, 14 parts stereopolylactic acid fiber and 6 parts additives, including toughening agents, fillers, lubricants, antioxidants and processing aids. The anti-slip layer contains the following components by weight: 45 parts waste tire pellets, 34 parts epoxy resin, 12 parts PPS fiber, 5 parts sulfur, and 4 parts modified carbon black. The surface layer is a blend of corn fiber, bamboo fiber, nylon fiber, and polypropylene fiber. The modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester, and ethanol. The preparation method of the modified starch is as follows: obtain corn starch and potato starch, pour them into 30 to 50 times their weight of deionized water, and stir at high speed using a mixer at 1300 rpm. During the stirring process, raise the temperature to 80°C and maintain... Stirring at room temperature for 15 minutes yields a starch microsphere emulsion. Acrylic acid, sorbitan fatty acid ester, and ethanol are added to a reaction vessel and stirred at 50°C and 500 rpm for 15 minutes. The starch microsphere emulsion is then added to the reaction vessel and stirred for another 30 minutes at 900 rpm. After cooling to room temperature, starch microspheres and the filtrate are obtained by suction filtration. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain modified starch. The raw materials for modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water. The preparation method of modified montmorillonite is as follows: under room temperature conditions... The following steps are performed: Montmorillonite is poured into a grinding device for grinding. During the grinding process, quaternary phosphine salt, sodium pyrophosphate, and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water, and ultrasonic treatment is performed using an ultrasonic device. After heating to 70°C, it is allowed to cool and settle naturally. Finally, it is filtered, centrifuged, washed, dried, and sieved to obtain modified montmorillonite. The preparation method for modified carbon black is as follows: Silane coupling agent and water are poured into a mixer and stirred to form a silane coupling agent solution. The pH value of the silane coupling agent solution is then adjusted to 4. After hydrolysis of the silane coupling agent, a silane coupling agent hydrolysate is formed. This hydrolysate is diluted in an ethanol solution, and the pH value is adjusted to 4. Then carbon black is added, mixed, and poured into a reaction vessel for stirring to obtain a slurry. The reaction vessel is heated to 75°C, and stirring is continued to allow the silane coupling agent to graft onto the carbon black surface. Finally, it is dried and pulverized to obtain modified carbon black. An intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber, and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Moreover, the combination of the surface layer, intermediate layer, and anti-slip layer, along with the internal reinforcing materials, can improve the carpet's low-temperature resistance.

[0028] A method for preparing a composite material automotive sound insulation carpet includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives and mix to obtain a mixture. Divide the mixture into three parts. Pour one part of the mixture into a honeycomb structure mold to make a honeycomb structure layer. The other two parts of the mixture are used to make a rubber sheet layer. The mixing speed is controlled at 600rpm~700rpm. The three parts of the mixture are evenly distributed. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: The waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black are mixed and then poured into a mold that can make anti-slip texture, and extruded to obtain an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

[0029] Composite material automotive sound insulation carpets are used in automobiles.

[0030] Reference Figure 1 Example 5 This embodiment proposes a composite material automotive sound insulation carpet, which includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 35 parts polypropylene resin, 25 parts polycarbonate, 10 parts modified starch, 10 parts modified montmorillonite, 15 parts stereopolylactic acid fiber and 5 parts additives, including toughening agents, fillers, lubricants, antioxidants and processing aids. The anti-slip layer comprises the following components by weight: 55 parts waste tire pellets, 25 parts epoxy resin, 11 parts PPS fiber, 5 parts sulfur, and 4 parts modified carbon black. The surface layer is a blend of corn fiber, bamboo fiber, nylon fiber, and polypropylene fiber. The modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester, and ethanol. The preparation method of the modified starch is as follows: obtain corn starch and potato starch, pour them into 30 to 50 times their weight of deionized water, and stir at high speed using a mixer at 1300 rpm. During the stirring process, the temperature is raised to 80°C and maintained. Stirring at room temperature for 15 minutes yields a starch microsphere emulsion. Acrylic acid, sorbitan fatty acid ester, and ethanol are added to a reaction vessel and stirred at 50°C and 500 rpm for 15 minutes. The starch microsphere emulsion is then added to the reaction vessel and stirred for another 30 minutes at 900 rpm. After cooling to room temperature, starch microspheres and the filtrate are obtained by suction filtration. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain modified starch. The raw materials for modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water. The preparation method of modified montmorillonite is as follows: under room temperature conditions... The following steps are performed: Montmorillonite is poured into a grinding device for grinding. During the grinding process, quaternary phosphine salt, sodium pyrophosphate, and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water, and ultrasonic treatment is performed using an ultrasonic device. After heating to 70°C, it is allowed to cool and settle naturally. Finally, it is filtered, centrifuged, washed, dried, and sieved to obtain modified montmorillonite. The preparation method for modified carbon black is as follows: Silane coupling agent and water are poured into a mixer and stirred to form a silane coupling agent solution. The pH value of the silane coupling agent solution is then adjusted to 4. After hydrolysis of the silane coupling agent, a silane coupling agent hydrolysate is formed. This hydrolysate is diluted in an ethanol solution, and the pH value is adjusted to 4. Then carbon black is added, mixed, and poured into a reaction vessel for stirring to obtain a slurry. The reaction vessel is heated to 75°C, and stirring is continued to allow the silane coupling agent to graft onto the carbon black surface. Finally, it is dried and pulverized to obtain modified carbon black. An intermediate layer is prepared by using polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolymer polylactic acid fiber, and additives. The intermediate layer adopts a honeycomb structure, which can form numerous sound-insulating cavities inside the intermediate layer to improve the sound insulation effect. Moreover, the combination of the surface layer, intermediate layer, and anti-slip layer, along with the internal reinforcing materials, can improve the carpet's low-temperature resistance.

[0031] A method for preparing a composite material automotive sound insulation carpet includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives and mix to obtain a mixture. Divide the mixture into three parts. Pour one part of the mixture into a honeycomb structure mold to make a honeycomb structure layer. The other two parts of the mixture are used to make a rubber sheet layer. The mixing speed is controlled at 600rpm~700rpm. The three parts of the mixture are evenly distributed. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: The waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black are mixed and then poured into a mold that can make anti-slip texture, and extruded to obtain an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

[0032] Composite material automotive sound insulation carpets are used in automobiles.

[0033] The carpets prepared in Examples 1 to 5 are compared with conventional carpets in the following table: sound insulation coefficient 0.56 0.96 0.97 0.96 0.96 0.94 -30℃ Low Temperature Multiaxial Impact Strength YU YD YD YD YD YD The sound insulation coefficient is tested in accordance with GB / T19889.1-2005; the low-temperature multiaxial impact strength is tested in accordance with ISO6603-2-2000: the multiaxial impact strength at -30℃ is tested, and the performance is divided into four grades from best to worst: YD, YS, YU, and NY.

[0034] As can be seen from the table above, the carpet prepared by the present invention has significantly improved sound insulation and low-temperature resistance, and embodiment two is the best embodiment.

[0035] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A composite material automotive sound insulation carpet, characterized in that, The composite automotive sound insulation carpet includes a surface layer, an intermediate layer bonded to the bottom of the surface layer, and an anti-slip layer bonded to the bottom of the intermediate layer. The intermediate layer includes a honeycomb structure layer and a rubber sheet layer bonded to the top and bottom of the honeycomb structure layer. The intermediate layer comprises the following components in parts by weight: 35 to 45 parts of polypropylene resin, 20 to 30 parts of polycarbonate, 10 to 20 parts of modified starch, 5 to 15 parts of modified montmorillonite, 5 to 15 parts of stereopolylactic acid fiber, and 5 to 10 parts of additives, including toughening agents, fillers, lubricants, antioxidants, and processing aids. The anti-skid layer contains the following components in parts by weight: 45 to 55 parts waste tire pellets, 25 to 35 parts epoxy resin, 10 to 20 parts PPS fiber, 5 parts sulfur and 4 parts modified carbon black. The surface layer is made of a blend of corn fiber, bamboo fiber, nylon fiber and polypropylene fiber; The modified starch is made from corn starch, potato starch, deionized water, acrylic acid, sorbitan fatty acid ester and ethanol. The modified starch is prepared as follows: corn starch and potato starch are obtained and poured into 30 to 50 times their weight of deionized water. The mixture is stirred at high speed using a mixer at a speed of 1200 rpm to 1500 rpm. During the stirring process, the temperature is raised to 80°C and kept at this temperature for 15 minutes to obtain a starch microsphere emulsion. Acrylic acid, sorbitan fatty acid ester, and ethanol are poured into a reaction vessel and stirred and mixed at 50°C at a speed of 500 rpm to 700 rpm. After 15 minutes, the starch microsphere emulsion is poured into the reaction vessel and stirred for another 30 minutes at a speed of 800 rpm to 900 rpm. The mixture is then cooled to room temperature and filtered to obtain starch microspheres and filtrate. The starch microspheres are dried and sieved through a 100-mesh sieve to obtain the modified starch. The raw materials for producing the modified montmorillonite include montmorillonite, quaternary phosphine salt, sodium pyrophosphate, sodium stearate, and deionized water. The modified montmorillonite is prepared as follows: montmorillonite is poured into a grinding device and ground at room temperature. During the grinding process, quaternary phosphine salt, sodium pyrophosphate and sodium stearate are added for dry grinding to obtain powder. The powder is dissolved in water and ultrasonic treatment is performed by starting an ultrasonic device. After heating to 70°C, it is allowed to cool and settle naturally. Finally, it is filtered, centrifuged, washed, dried and sieved to obtain the modified montmorillonite. The modified carbon black is prepared as follows: Silane coupling agent and water are poured into a mixer and stirred to form a silane coupling agent solution. The pH value of the silane coupling agent solution is then adjusted to 4. After the silane coupling agent is hydrolyzed to form a silane coupling agent hydrolysate, it is diluted in an ethanol solution and the pH value is adjusted to 4. Then carbon black is added, mixed, and poured into a reaction vessel for stirring to obtain a slurry. The reaction vessel is heated to 75°C and the stirring reaction continues to allow the silane coupling agent to graft onto the surface of the carbon black. Finally, the mixture is dried and pulverized to obtain the modified carbon black.

2. A method for preparing a composite material automotive sound insulation carpet as described in claim 1, characterized in that, Includes the following steps: S1: Weigh the raw materials for the intermediate layer: polypropylene resin, polycarbonate, modified starch, modified montmorillonite, stereopolylactic acid fiber and additives. Put the polypropylene resin, polycarbonate, modified starch and modified montmorillonite into an extruder, and extrude the raw material granules after melting, mixing and homogenizing. S2: Heat and melt the raw material particles, add the three-dimensional polylactic acid fiber and additives to mix, and divide the mixture into three parts. One part of the mixture is poured into the honeycomb structure mold to make a honeycomb structure layer, and the other two parts of the mixture are made into a plastic sheet layer. S3: Bond two layers of adhesive sheets to a honeycomb structure layer to form a sandwich structure, thus obtaining the middle layer; S4: Mix waste tire pellets, epoxy resin, PPS fiber, sulfur and modified carbon black, then pour into a mold that can make anti-slip texture, and extrude to form an anti-slip layer. S5: Adhere the top layer to the top of the middle layer and the anti-slip layer to the bottom of the middle layer to obtain a composite automotive sound insulation carpet.

3. The method for preparing a composite material automotive sound insulation carpet according to claim 2, characterized in that, In step S2, the mixing speed is controlled at 600 rpm to 700 rpm, and the three mixtures are evenly divided.

4. The composite material automotive sound insulation carpet as described in claim 1 is used in automobiles.

Citation Information

Patent Citations

  • Processing method of automotive carpet, automotive carpet and vehicle

    CN116038962A

  • A carpet for car boots

    CN206306555U

  • Automobile carpet with good sound insulation effect

    CN213007781U